Bioprospecting and biodiversity investigations of endophytic fungi isolated from Juniperus communis - Vigneshwari, Aruna; Škrbić, Biljana D.; Kredics, László; Abbas, Lubna; Bakacsy, László; Vágvölgyi, Csaba; Szekeres, András (Acta Biologica Szegediensis, 2021)
Endophytes are a group of highly diverse microorganisms that reside within plant tissues without causing obvious symptoms on the host. In our study, Juniperus communis samples were collected from Hungary and used for the isolation of endophytic fungal strains. From 240 plant samples, 76 fungal isolates were recovered and subcultured for homogeneity. The isolates were identified using molecular taxonomical tools at the genus level and their biodiversity parameters were determined. The taxonomic diversity of the isolates was remarkably high, and the most abundant genera were Fusarium, Alternaria and Trichoderma. The secondary metabolites produced by the isolated endophytic fungi were extracted both from their mycelia and their ferment broth and their antimicrobial activities were tested against bacteria, yeasts, and filamentous fungi. In the antimicrobial tests, a total of 58 strains showed antimicrobial activity against at least one test organism. Altogether, 6.67% of the isolates have antibacterial effects with wide spectrum, and 10 strains showed remarkably high inhibitory percentage against yeast, while the extracts of 11 isolates proved to be active against filamentous fungi.